Treatment outcome of pneumonia and its associated factors among pediatric patients admitted to Hiwot Fana Comprehensive Specialized University Hospital, Eastern Ethiopia - Adbela, Gebremariam; Abdurahman, Hanan; Hailu, Saba; Keneni, Mulualem; Mohammed, Ahmed; Weldegebreal, Fitsum (Frontiers in Pediatrics, 2024)
Background: Pneumonia is the leading cause of morbidity and mortality among children worldwide. Despite its substantial impact, there theexists a dearth of evidence regarding treatment outcomes and related factors, particularly within the Ethiopian context. This study endeavors to address these critical gaps by examining the treatment outcome of pneumonia among pediatric patients hospitalized in Hiwot Fana Comprehensive Specialized University Hospital.high burden of the disease, evidence related to treatment outcomes of pneumonia and associated factors is limited in Ethiopia. This study seeks to fill the existing practical gaps by assessing the treatment outcome of pneumonia among pediatric patients hospitalized in Hiwot Fana Comprehensive Specialized University Hospital.Method-A facility-based cross-sectional study was conducted on 204 children (≤14 years of age) diagnosed with pneumonia and admitted to Hiwot Fana Comprehensive Specialized UniversityHospital. An interview using a structured questionnaire accompanied by a review of medical records was used to collect data from the parents/guardians. A binary logistic regression model with an adjusted odds ratio (aOR) and a 95% confidence interval (CI) was used to identify the associated factors with the outcome variable. Statistical significance was set at P < 0.05 in multivariate analysis.Result-Among the 204 children (≤ 14 years) included in the study, 119 (93.6%, 95% CI: 90.2 -96.9) pneumonia patients survived whereas 13 (6.4%, 95% CI: 3.1-9.7) died. In multivariate logistic regression analysis, after adjusting for potential confounders it revealed children who had malnutrition (aOR=3.5, 95% CI 2.37-12.44), unvaccinated (aOR= 3.41, 95% CI 2.25-11.87), altered mental state during admission (aOR=4.49, 95% CI 2.28 -17.85), and complicated types of pneumonia (aOR=5.70, 95% CI 2.98-15.09) were independently associated with mortality.Poor treatment outcome was 6.4% among pediatric patients admitted with pneumonia in this study setting. Being unvaccinated, malnourished, and admitted with a complicated type of pneumonia as well as altered consciousness at the time of admission were significantly associated with poor treatment outcomes. These findings underscore the critical need to prioritize preventative measures against malnutrition and unvaccinated status in children. Early identification of such children and proper interventions are imperative to reduce such outcomes, particularly in resource-constrained settings.